PROBLEMATIKA SISTEM PENDIDIKAN DI INDONESIA - Mohammad Luthfi; Muhammad Fathin Abdul Ghoffar; Sukari (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
Education is the primary foundation for human resource development and the progress of a nation. However, the Indonesian education system still faces various complex and multidimensional problems. This article aims to comprehensively analyze the challenges of the Indonesian education system from a structural, cultural, managerial, infrastructure, and educational policy perspective. The research method used is qualitative research with a library research approach. Data sources were obtained from national education policy documents, reports from international institutions, and relevant previous research. The study indicates that the challenges facing education in Indonesia include unequal access to education, uneven teacher quality, curriculum instability, weak educational management, a low literacy culture, and gaps in educational technology. These challenges directly impact the low quality of graduates and the nation's competitiveness. Therefore, efforts to improve the education system are needed in an integrated, sustainable, and collaborative manner between the government, educational institutions, the community, and the business world.